Environmental and perceived stress in Australian dental undergraduates: Preliminary outcomes - Shannon Astill; Nikelle Ricketts; Love-Amrit Singh; Dylan Kurtz; Yong Hoon Gim; Boyen Huang (Tabriz University of Medical Sciences, 2016)
Background. Dental students have reported a high prevalence of psychological stress and the causes are associated with the challenging dental environmental and demographic factors. This study aimed to conduct a preliminary investigation on dental students' stress status, using a sample of first-to-third-year Bachelor of Dental Surgery students in an Australian university. Special interests included causes of dental environmental stress and access to help services. Methods. A sample of 145 students was surveyed with a modified Dental Environmental Survey and Depression Anxiety Stress Scale in 2014. The participants' demographic information was also collected. Results. The response rate was 95.4%. Second-year (P = 0.042), third-year (P < 0.001) and employed students (P = 0.027) were more likely to report stress resulting from transition to clinical learning. Third-year students were more often stressed about communicating and approaching staff (P = 0.023) as well as different opinions between staff (P < 0.001) and reduced holidays (P < 0.001). Students that were younger than 21 years of age (P = 0.001), that were first years (P < 0.001), and that were not in a relationship (P = 0.010) more often found difficulty of course work stressful. Students who were not in a relationship more often considered learning manual dexterity a source of stress (P = 0.034). Students previously seeking professional help were more likely to be stressed (P = 0.010). Conclusion. Causes of dental environment stress varied among years of study and demographic backgrounds. Professional support to stressed students should be enhanced. Further investigation is indicated.